1997
DOI: 10.1016/s0092-8674(00)80492-4
|View full text |Cite
|
Sign up to set email alerts
|

Transient Inhibition of Histone Deacetylation Alters the Structural and Functional Imprint at Fission Yeast Centromeres

Abstract: Histone acetylation may act to mark and maintain transcriptionally active or inactive chromosomal domains through the cell cycle and in different lineages. A novel role for histone acetylation in centromere regulation has been identified. Exposure of fission yeast cells to TSA, a specific inhibitor of histone deacetylase, interferes with repression of marker genes in centromeric heterochromatin, causes chromosome loss, and disrupts the localization of Swi6p, a component of centromeric heterochromatin. Transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
282
2
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 353 publications
(297 citation statements)
references
References 40 publications
12
282
2
1
Order By: Relevance
“…Recently, a study with mutant Tetrahymena strains harboring unphosphorylatable H3 histone demonstrated that Ser-10 phosphorylation is essential for proper chromosome condensation and segregation (Wei et al, 1999). Moreover, in fission yeast a prolonged exposure to trichostatin A (TSA), a specific histone deacetylase inhibitor (Yoshida et al, 1995) was shown to lead to H3 and H4 hyperacetylation in centromeric heterochromatin, derepression of reporter genes in centromeric regions, and chromosome loss (Ekwall et al, 1997). Finally, treatment of mouse cells with TSA for several days induced a relocation of pericentromeric heterochromatic blocks to the nuclear periphery, defective association of heterochromatin protein 1 (HP1) to pericentromeric regions, centromere-positive micronuclei, and abnormal anaphases (Taddei et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study with mutant Tetrahymena strains harboring unphosphorylatable H3 histone demonstrated that Ser-10 phosphorylation is essential for proper chromosome condensation and segregation (Wei et al, 1999). Moreover, in fission yeast a prolonged exposure to trichostatin A (TSA), a specific histone deacetylase inhibitor (Yoshida et al, 1995) was shown to lead to H3 and H4 hyperacetylation in centromeric heterochromatin, derepression of reporter genes in centromeric regions, and chromosome loss (Ekwall et al, 1997). Finally, treatment of mouse cells with TSA for several days induced a relocation of pericentromeric heterochromatic blocks to the nuclear periphery, defective association of heterochromatin protein 1 (HP1) to pericentromeric regions, centromere-positive micronuclei, and abnormal anaphases (Taddei et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In fission yeast, the formation of a heterochromatic structure is essential for full centromere function (13). The induction of histone hyperacetylation using the deacetylase inhibitor trichostatin A (TSA) 1 causes chromosome loss and the disruption of the fission yeast heterochromatin protein Swi6 association from pericentric regions, interfering with the transcriptional repression in centromeric heterochromatin resulting in the expression of reporter genes (14). Similarly, in human cells, prolonged treatment with TSA disrupts Swi6 homologue HP1 localization and causes centromeric defects resulting in chromosomal missegregation (11).…”
mentioning
confidence: 99%
“…Reversible chromosome condensation limits transcriptional machinery access to chromosomal DNA and inactivates chromatin remodeling complexes (Krebs et al, 2000). A recent study showed that treatment of fission yeast with TSA, a specific inhibitor of histone deacetylases (HDACs), induced the hyperacetylated state in centromeric chromatin causing chromosome loss, and disruption of swi6p localization, a component of centromeric heterochromatin (Ekwall et al, 1997). It has also been shown that the dynamic equilibrium between HAT and HDAC activities dramatically changes during mitosis and that the acetylated histones, gradually decreased during the early stages of mitosis, were absent in the metaphase and anaphase, and then gradually increased in the late mitotic phase (Kruhlak et al, 2001).…”
mentioning
confidence: 99%